Modélisation de la production de l'huître Crassostrea gigas du bassin de Marennes-Oléron (France). Etude de l'influence des apports de nitrates du fleuve Charente sur la production primaire et ostréicole - Raillard, Olivier; Menesguen, Alain (Counc. Meet. of the Int. Counc. for the Exploration of the Sea, La Rochelle (France), 26 Sep-4 Oct 1991, 1991)
Oyster production of the Marennes-Oléron Basin is simulated using a model integrating phytoplankton growth, oyster growth and horizontal transport of suspended matter. Firstly the simulations are compared to the measurements. At season scale, the phytoplankton and nitrates evolution are well predicted by the model. In compensation, the model does not simulated well the spring/neap tidal variability of the phytoplankton. Secondly, the phytoplancton and oyster productions are calculated as a function of the nitrates river inputs. Biotic capacity of the basin appears to be particulary influenced by these nutrients during summer. On the other hand, spatial variability of the impact of the nitrates variation is clearly shown, the primary productions of the north and north-west areas are poorly related to the nutrients from the river. In the north-east of the basin the high phytoplanktonic activity and the river proximity maintain to a quiet high level the sensitivity production. In the oyster production area, the responses of the primary and oyster productions to nitrate variation are non-linear : the sensitivity is more pronunced when decreasing nitrates than increasing. The trophics level of the center part and the east part of this area are the most river dependent. The growth of the total primary and oyster productions predicted by the model for an increasing nitrate inputs, point out a limited fertilization of the basin by the river. However, the incertainty of the present model call into question this results quality. La production ostréicole du bassin de Marennes-Oléron est simulée à partir d'un modèle qui intègre la croissance phytoplanctonique, la croissance de l'huître Crassostrea gigas et le transport particulaire et dissous. Dans un premier temps, la confrontation des calculs avec les mesures indiquent que le modèle reproduit correctement l'évolution des nitrates et de la chlorophylle à l'échelle de la saison. En revanche les oscillations vives-eaux / mortes-eaux des teneurs chlorophylliennes sont ...